Using The Goal Programming Model To Plan Human And Medical Material Resources In The Medical Sector An Applied Study On The Chemotherapy And Radiotherapy Center At Tishreen University Hospital In Lattakia - الجبيلي , راميا; نصره , زين العابدين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The health sector is one of the most important and effective sectors in every country, and the optimal allocation of resources in this sector is important to reduce the high cost of health care, as decision makers in the health system, especially in hospitals, face limited resources and unlimited needs. The aim of this research is to develop the performance of the Chemotherapy and Radiotherapy Center in Tishreen University Hospital in Lattakia, using the programming objectives method, on the data for the year 2019 related to the medical human and material resources at the Chemotherapy and Radiotherapy Center, in order to be processed with the Win QSB program to obtain the best distribution of these resources. The researcher reached to build a linear goal programming model to allocate human and medical material resources in an optimal manner in the chemotherapy and radiotherapy center, and to make proposals for developing work in this center, as it was found from the application of the goal programming method that there is an untapped increase in some of these resources (specialist doctors 7, nurses 73, Physicists 2, x-ray technicians 11, leather chairs 4, rooms 2, clinics 3, pressure devices 4, headphones 3, ambu 1, air brushes 1), speed and flexibility in dealing with any change in the data thanks to the results of the sensitivity analysis of the model.